2017
DOI: 10.1007/s10120-017-0762-1
|View full text |Cite
|
Sign up to set email alerts
|

How to adjust endoscopic findings to histopathological findings of the stomach: a “histopathology-oriented” correspondence method helps to understand endoscopic findings

Abstract: The histological structure of gastric cancers of the same histological subtype may not be similar. One-to-one correspondence between endoscopic images and gastric mucosal histology (histopathology-oriented correspondence) will improve endoscopic diagnosis and provide more useful information for pathological diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Yao et al examined the detailed relationship between endoscopic and histological findings by investigating the length of the intervening section and the depth of the glands (3). Fujita et al described a systematic process, the KOTO method, which allows detailed adjustments of endoscopic findings to match histopathological findings (32). The present study demonstrated that our light transmission-assisted pathological examination helped endoscopists and pathologists to easily and accurately understand the nature, depth, and extent of the lesions.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Yao et al examined the detailed relationship between endoscopic and histological findings by investigating the length of the intervening section and the depth of the glands (3). Fujita et al described a systematic process, the KOTO method, which allows detailed adjustments of endoscopic findings to match histopathological findings (32). The present study demonstrated that our light transmission-assisted pathological examination helped endoscopists and pathologists to easily and accurately understand the nature, depth, and extent of the lesions.…”
Section: Discussionmentioning
confidence: 55%
“…Fujita et al. described a systematic process, the KOTO method, which allows detailed adjustments of endoscopic findings to match histopathological findings ( 32 ). The present study demonstrated that our light transmission-assisted pathological examination helped endoscopists and pathologists to easily and accurately understand the nature, depth, and extent of the lesions.…”
Section: Discussionmentioning
confidence: 99%